2019
DOI: 10.1038/s41467-019-12501-1
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for the activation of the mechanosensitive Piezo1 channel by the small molecule Yoda1

Abstract: Mechanosensitive Piezo1 and Piezo2 channels transduce various forms of mechanical forces into cellular signals that play vital roles in many important biological processes in vertebrate organisms. Besides mechanical forces, Piezo1 is selectively activated by micromolar concentrations of the small molecule Yoda1 through an unknown mechanism. Here, using a combination of all-atom molecular dynamics simulations, calcium imaging and electrophysiology, we identify an allosteric Yoda1 binding pocket located in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
185
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(199 citation statements)
references
References 56 publications
(64 reference statements)
14
185
0
Order By: Relevance
“…The Piezo1 conformational changes induced by channel clustering has two major components: a flattening of the whole arm when viewed parallel to the membrane and a straightening of the proximal N-terminal region (rotation around the elbow) when viewed perpendicular to the membrane ( Figure 1d ). These conformational changes observed here due to membrane flattening are similar to the ones observed from a truncated Piezo1 simulation when applying membrane tension ( 11 ). There are three helical bundles (Piezo repeats) on the N-terminal peripheral region of the arms not present in Piezo1 cryo-EM structures.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The Piezo1 conformational changes induced by channel clustering has two major components: a flattening of the whole arm when viewed parallel to the membrane and a straightening of the proximal N-terminal region (rotation around the elbow) when viewed perpendicular to the membrane ( Figure 1d ). These conformational changes observed here due to membrane flattening are similar to the ones observed from a truncated Piezo1 simulation when applying membrane tension ( 11 ). There are three helical bundles (Piezo repeats) on the N-terminal peripheral region of the arms not present in Piezo1 cryo-EM structures.…”
Section: Discussionsupporting
confidence: 83%
“…Our previous proof-of-concept AA simulation showed that the membrane curvature, or lipid dome, imposed by the resting conformation of a truncated Piezo1 takes place over 3 μs ( 11 ). To reduce computational time, here we first used a 12 μs Coarse-Grained (CG) Martini simulation to enable rapid lipid diffusion and dome formation while the Piezo1 backbone was kept rigid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the extended structure obtained at −40 bar is corroborated by recent structural data which positively correlate the size of the vesicle with a flattened Piezo1 structure13. Flattening of Piezo1 may also be needed for Yoda1 binding 17 .…”
Section: Tension Causes Piezo1 To Flatten and Expandmentioning
confidence: 99%